Tungsten Infused Grain Boundaries Enabling Universal Performance Enhancement of Co-Free Ni-Rich Cathode Materials. Issue 12 (6th December 2021) - Rathore, Divya; Geng, Chenxi; Zaker, Nafiseh; Hamam, Ines; Liu, Yulong; Xiao, Penghao; Botton, Gianluigi A.; Dahn, Jeff; Yang, Chongyin
Abstract : Ni-rich cathode materials suffer from poor capacity retention due to micro-cracking and interfacial reactivity with electrolyte. Addition of tungsten (W) to some Ni-rich materials can improve capacity retention. Here, a WO3 surface coating is applied on Ni-rich hydroxide precursors before heating with lithium hydroxide. After heating in oxygen, Ni-rich materials with any of the commonly used dopants (magnesium, aluminum, manganese, etc.) show a "universal" improvement in capacity retention. Experimental characterization and theoretical modelling showed W was concentrated in the grain boundaries between the primary grains of secondary particles of the layered oxides, and W is incorporated in amorphous Lix Wy Oz phases rather than as a substituent in the LiNiO2 lattice. This self-infusion of W in the grain boundaries during synthesis also significantly restricts primary crystallite grain growth. Along with smaller primary grain size, the Lix Wy Oz phases in the grain boundaries lead to improved resistance to microcracking and reduced surface or interfacial reactivity. Improving the intrinsic properties of primary grains through doping of Mg, Al, or Mn and reinforcing the secondary particle structure mechanically and chemically using W or a similar element, M, that forms Lix MOy phases and does not substitute into LiNiO2 is a universal strategy to improve polycrystalline Ni-rich materials.